2020
DOI: 10.1080/23744731.2020.1827867
|View full text |Cite
|
Sign up to set email alerts
|

Using long-term measurements of airflow, electrical power, indoor temperature, and CO 2 -concentration for evaluating sizing and performance of an all-air HVAC system in an office building - a case study

Abstract: Monitoring performance of heating, ventilation and air-conditioning (HVAC) during building operation enables to evaluate the appropriateness of the system's design. Such insights can help to reduce energy consumption while ensuring satisfying indoor conditions in the monitored building. Additionally, such insight can help to improve future HVAC design. The aim of this paper is to present a case study demonstrating how HVAC engineers can evaluate whether the monitored air-handling units (AHUs) were appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…To ensure that the additive model developed produces reasonable results, the peak total cooling loads calculated through EnergyPlus simulation and the 3 There are four levels at orientation: N, E, W, S 4 The window area ratio is the ratio of the window area to the floor area of the perimeter zones 5 Parameters used in model validation only additive model for these 1000 cases were compared. The quality of the developed model was evaluated by mean bias error (MBE), coefficient of variation (CV), and coefficient of determination (R 2 ), as shown in Equations ( 8)- (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that the additive model developed produces reasonable results, the peak total cooling loads calculated through EnergyPlus simulation and the 3 There are four levels at orientation: N, E, W, S 4 The window area ratio is the ratio of the window area to the floor area of the perimeter zones 5 Parameters used in model validation only additive model for these 1000 cases were compared. The quality of the developed model was evaluated by mean bias error (MBE), coefficient of variation (CV), and coefficient of determination (R 2 ), as shown in Equations ( 8)- (10).…”
Section: Methodsmentioning
confidence: 99%
“…Djunaedy et al [2] found that it is not uncommon for systems to be oversized by up to 100%. Right-sized equipment reduces the first cost, extends the life span of equipment and future replacement costs, reduces energy use, and improves occupants' comfort condition [3].…”
Section: Introductionmentioning
confidence: 99%